Nurturing Awareness and Responsible Practices in E-waste Management - Vayadande, Kuldeep; Jadhav, Amol; Bailke, Preeti; Bodhe, Yogesh Uttamrao; D. Magar, Hanmant; Kulkarni, Isha; Deshpande, Neha; Jadhav, Pranav; Kulkarni, Sai; Sagarkar, Sayali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Nowadays, people use electronic devices everywhere and all the time. Though they prove to improve our quality of everyday life, there also stands a challenge which is electronic waste (e-waste). The constantly expanding technology and unawareness among people about its severe effects remains a problem. Many harmful substances like mercury, barium and lead are found in e-waste and a huge amount of e-waste is generated consistently and if not urgently addressed it would show consequences by affecting our mother earth, our environment and health. Hence, our website "E-waste Facility locator" aims to contribute to proper e-waste management and responsible disposal. This issue demands attention and hence, we aim to develop a website that would increase the awareness among people of the e-waste and its effects. Our website focuses towards helping people find e-waste facilities and recycling centers nearby to their location which would increase the use of suitable e-waste disposal methods. We will also integrate an image identification model that would identify the e-waste item based on the image uploaded by the user and assist the user by suggesting a list of solutions on how to correctly dispose that off. Our website mainly focuses towards increasing awareness among people of the adverse effects of e-waste.